Evaluation of Pyrolysis Oil as Carbon Source for Fungal Fermentation - Dörsam, Stefan; Kirchhoff, Jennifer; Bigalke, Michael; Dahmen, Nicolaus; Syldatk, Christoph; Ochsenreither, Katrin (Frontiers in Microbiology, 2016)
Pyrolysis oil, a complex mixture of several organic compounds, produced during flash pyrolysis of organic, lignocellulosic material was evaluated for its suitability for the fermentation of filamentous fungi as an alternative carbon source. Several fungi were tested on tolerance and Aspergillus oryzae and Rhizopus delemar, both established organic acid producer, are used as model organisms for evaluation of pyrolysis oil as carbon source for fungal fermentation. Toxicity tests showed that A. oryzae tolerates pyrolysis oil contents between 1 % or 2 % depending on stationary production phase or growth phase respectively. To investigate the reason for the low tolerance level, eleven substances from pyrolysis oil, like aldehydes, organic acids, phenols and other compounds were chosen and the maximum concentration determined where growth and malic acid production is still possible. Furthermore, the effects of substances to the malic acid production curves were analyzed and the compounds were divided on this property in three groups of toxicity. To validate the results a selection of tests were done with R. delemar. Small amounts of phenolic substances were observed to be beneficial for malic acid production, whereas higher amounts decreased production. Furthermore, hints for isoeugenol degradation by A. oryzae could be observed for the first time. Additionally, 2-Cyclopenten-1-on was identified to be possibly responsible for the growth tolerance limit of pyrolysis oil. Similar to 2-Cyclopenten-1-on, Isoeugenol is only tolerated in very low concentrations for R. delemar.